Navigating Uncertainty: Evaluating the Pandemic's Impact on Warung Upnormal's Expansion Strategy - Alanudin, Dian; Miqdad Robbani, Muhammad (Ridwan Institute, 2024)
The COVID-19 pandemic presented significant challenges to the food and beverage industry, impacting consumption patterns and economic dynamics. This research aims to evaluate the impact of the COVID-19 pandemic on the expansion strategy of Warunk Upnormal, one of the leading restaurant chains in Indonesia. This research employs a case study approach to explore the impact of the COVID-19 pandemic on the food and beverage industry in Indonesia. the pandemic led to a 40% decline in sales, necessitating adaptations like transitioning to take-away-only operations. While foot traffic gradually recovered post-pandemic, changing consumer preferences prompted the closure of multiple outlets. Financial strains exacerbated by the franchise model underscored the delicate balance between profitability and operational sustainability. Similarly, other startups like Kopi Kenangan faced challenges despite alternative business strategies. Roy Mandey of the Indonesian Retailers Association emphasizes the importance of adaptability and innovation in navigating volatile market conditions. Sustained innovation and a deep understanding of evolving consumer preferences will be crucial for future success in the post-pandemic landscape.